Healthcare Services, Delivery, and Financing 2023
DOI: 10.1370/afm.21.s1.3873
|View full text |Cite
|
Sign up to set email alerts
|

High Quality Primary Care, Stress, and Major Practice Changes

Abstract: Context: High quality primary care results in longer lives and more equity. Despite its high value, primary care is under-resourced and under perpetual stress. Clearly the COVID pandemic was a major stress, and the long-term impacts are still being felt by practices.Objective: We sought to assess the current state of stress in primary care and how it has impacted the provision of high-quality care.Study Design: Mixed methods evaluation of practice surveys and semi-structured interviews.Population studied: Ever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…11 In addition, primary care settings are affected by the high patient-to-provider ratio and the fear of lower-quality care due to a decreasing number of providers. 11 The additional stress of the COVID-19 pandemic was revealed in a qualitative study in which interviews of 33 primary care staff members showed that although the initial response to the pandemic resulted in support from management, development opportunities, and feelings of being needed, as the pandemic became a chronic stressor, staff showed more characteristics of burnout. 12 In a qualitative study, primary care nurses and physicians identified several challenging work issues and sources of stress, including collaboration barriers, technology and documentation problems, unreasonable work tasks, lack of access to necessary resources, and increased workload.…”
Section: Resiliency Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…11 In addition, primary care settings are affected by the high patient-to-provider ratio and the fear of lower-quality care due to a decreasing number of providers. 11 The additional stress of the COVID-19 pandemic was revealed in a qualitative study in which interviews of 33 primary care staff members showed that although the initial response to the pandemic resulted in support from management, development opportunities, and feelings of being needed, as the pandemic became a chronic stressor, staff showed more characteristics of burnout. 12 In a qualitative study, primary care nurses and physicians identified several challenging work issues and sources of stress, including collaboration barriers, technology and documentation problems, unreasonable work tasks, lack of access to necessary resources, and increased workload.…”
Section: Resiliency Literature Reviewmentioning
confidence: 99%
“…Primary care is a high stress health care work setting due to the mission of offering comprehensive care and improving access to vulnerable populations with limited resources 11. In addition, primary care settings are affected by the high patient-to-provider ratio and the fear of lower-quality care due to a decreasing number of providers 11.…”
Section: Resiliency Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation